Efeito da aplicação tópica de peróxido de hidrogênio sobre a superfície e interface esmalte: restaurações odontológicas - Rodrigo Aliprandi Dutra (2003)
This study intends to analise the superficial roughtness and the interface between amalgam, glass ionomer cement, compomer, porcelain and gold, after the 35% hidrogen peroxideaplication, through bidimensional perfilometry and scaning electron microscopy. There were used 36 human bicuspids, wich had class V cavity in their buccal surfaces. This cavities were restored with restorative materials bellow, and stand out that the conjunt of enamel and restorative materials were submited to a treatment with 35% hidrogen peroxide.This material was aplied 7 times each one, during 30 minutes, with intervals of 24 h between the aplications. The perfilometric analisys before and after the treatment was done in each specimen, achieved the roughtness average valors and skewness. A treated specimen and one non-treated specimen of each group of restorative material were analisedin a scaning electron microscopy. There was not alteration at the interface between the enamel and composite resin, amalgam, glass ionomer cement, compomer, porcelain and gold restorations. The enamel and composit resin showed a surface topografy alteration. Amalgam restoration showed increase in the roughtness average. Glass ionomer cement restoration had their matrix etched by the bleaching agent, showing a increase in the number of trine at their surface. Compomer, gold and porcelain restorations did not suffer any alterations after the treatment.